KLEPTOCRACY OF BRIBERY IN PROMOTING POSITION IN INDONESIA THE PERSPECTIVE OF THE SOCIOLOGY OF LAW - Muhibin, Mochamad; Nasution, Eli Sanur; Bima, Ghandi (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Clean Government and Good Governance has realized yet in Indonesia. It isproven by selling and purchasing the positions in various places still exist. Theprocess of rotation, transfer, and promotion of civil servant (ASN) that shouldhave been given to the competent employees did not run as it should. The fieldinvestigation shows that the existence of power transaction that makes positionas an object of commerce. This article aims to examine the kleptocracy of sellingand purchasing the positions in Indonesia. The perspective used is the sociologyof law. The research methodology implements a normative legal methodologythrough a qualitative approach and analysis of the fraud triangle theory, Gonetheory, Ramirez Torres theory and Icebery Model theory. The result of the studyconcludes that bureaucrats are often not transparent, corrupt and tend to carryout transactional practices. For this reason, it is necessary to change therecruitment system and overall monitoring of civil servant (ASN) bureaucracy.